2001
DOI: 10.1111/1467-8535.00198
|View full text |Cite
|
Sign up to set email alerts
|

VICAID: Development and evaluation of a palmtop‐based job aid for workers with severe developmental disabilities

Abstract: The development of technologies to assist people with severe and profound developmental disabilities to engage in constructive activity without constant support from carers may assist such persons to participate fully in vocational and other occupational activities. We describe the development, evaluation and use of VICAID, a system based on a radically simplified palmtop computer. The VICAID system enables a person with a developmental disability to access pictorial instructions designed to help him or her in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…A relatively common criterion for determining the capacity to recognize graphic symbols (Keogh & Reichle 1985; Reichle & Keogh 1985; Mirenda & Locke 1989) is 80% or more matches between object and picture, which is also in line with more recent studies (e.g. Furniss et al. 2001; Sigafoos et al.…”
Section: Methodssupporting
confidence: 77%
“…A relatively common criterion for determining the capacity to recognize graphic symbols (Keogh & Reichle 1985; Reichle & Keogh 1985; Mirenda & Locke 1989) is 80% or more matches between object and picture, which is also in line with more recent studies (e.g. Furniss et al. 2001; Sigafoos et al.…”
Section: Methodssupporting
confidence: 77%
“…James and Hammersley () reported on testing of ICT solutions for the hearing‐impaired, Hartley () investigated designing instructional text for older readers, and Seale () investigated the use of personal web pages for adults with Down syndrome. Studies with adults with severe cognitive disability have reported on the use of computer pictorial instructions to provide support in the job environment (Furniss et al , ) and on computer‐supported daily organiser application testing (Ager & Aalykke, ). For people with acquired brain injury, computer‐aided relearning activity has been tested by experiment, with the control group using traditional methods.…”
Section: Discussionmentioning
confidence: 99%
“…This was noted as helping their independence and self-confidence (Davies et al 2002a(Davies et al , 2002b. A similar program called VICAID is a palmtop-based job aid for workers with such difficulties which can be used for task scheduling, for example to assemble a valve in 26 stages, which can also be useful for those with attentional difficulties (Furniss et al 2001) • motor impairments such as muscular dystrophy where movement is difficult and the handheld function of word prediction is useful (Myers 2000).…”
Section: Palmtops and Special Needsmentioning
confidence: 99%